ChemInform Abstract: Catalytic Activity of the Nanoporous MCM‐41 Surface for the Paal—Knorr Pyrrole Cyclocondensation. Issue 45 (November 2015) - Aghapoor, Kioumars; Amini, Mostafa M.; Jadidi, Khosrow; Mohsenzadeh, Farshid; Darabi, Hossein Reza
Abstract Nanoporous silica (MCM‐41) displays an extraordinary high catalytic activity in the Paal—Knorr synthesis.